2017
DOI: 10.1080/19396368.2017.1358774
|View full text |Cite
|
Sign up to set email alerts
|

In vitroeffects of melatonin on colonization of neonate mouse spermatogonial stem cells

Abstract: We have recently reported that antioxidant supplements enhance the efficacy of cryopreserved spermatogonial stem cells. Melatonin is considered a free radical scavenger which has direct and indirect antioxidant effects in in vitro and in vivo microenvironments. Due to the anti-apoptotic properties of melatonin, researchers have proposed that melatonin may improve the efficiency of spermatogonial stem cell (SSC) transplantation. However, the appropriate methodology which facilitates SSC proliferation remains to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…According to these findings in goat SSCs, MLT was found to promote beneficial effects in terms of cell proliferation and survival rates in mice SSCs [ 98 ].…”
Section: Melatonin In Stem Cells Cytoprotectionmentioning
confidence: 99%
“…According to these findings in goat SSCs, MLT was found to promote beneficial effects in terms of cell proliferation and survival rates in mice SSCs [ 98 ].…”
Section: Melatonin In Stem Cells Cytoprotectionmentioning
confidence: 99%
“…In addition, it has been shown that the melatonin acts as a cryoprotectant in the freezing media containing sperm and positively affects male fertility preservation [ 20 22 ]. Previous research has shown that adding melatonin to the culture medium increases the efficiency and performance of SSCs isolated from mice [ 15 , 16 ]. Cryopreservation of SSCs can provide appropriate options such as SSCs transplantation and in vitro spermatogenesis for prepubertal boys and adult male after cancer treatment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This drug has antioxidant and antiapoptotic properties that rely on the radical scavenger effect delivered by its indole derivate [ 84 ]. While melatonin appeared to be beneficial in SSC transplantation experiments [ 85 , 86 ], addition of melatonin to the vitrification-warming medium did not reduce expression of apoptotic genes in frozen/thawed murine ITT [ 87 ].…”
Section: Resultsmentioning
confidence: 99%